2021
DOI: 10.1101/2021.02.16.21251849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convalescent plasma for preventing critical illness in COVID-19: A phase 2 trial and immune profile

Abstract: Rationale: The COVID-19 pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an unprecedented event requiring rapid adaptation to changing clinical circumstances. Convalescent immune plasma (CIP) is a promising treatment that can be mobilized rapidly in a pandemic setting. Objectives: We tested whether administration of SARS-CoV-2 CIP at hospital admission could reduce the rate of ICU transfer or 28 day mortality. Methods: In a single-arm phase II study, patients >18 years… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…There were 13 RCTs, of which four were categorized as Oxford LoE 2 [25,26,28,33], seven were downgraded to Oxford LoE 3 [21][22][23][29][30][31][32], and two to Oxford LoE 4 [24,27]. Of the remaining papers, eight were prospective controlled clinical trials, of which three were categorized as Oxford LoE 3 [34,35,50], four as Oxford LoE 4 [46,48,53,55], and one as Oxford LoE 5 [37]. Of the 16 matched case-control series, 14 were categorized as Oxford LoE 4 [20, 36, 38-41, 43, 44, 47, 49, 51, 52, 54, 56] and two as Oxford LoE 5 [42,45].…”
Section: General Information On Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 13 RCTs, of which four were categorized as Oxford LoE 2 [25,26,28,33], seven were downgraded to Oxford LoE 3 [21][22][23][29][30][31][32], and two to Oxford LoE 4 [24,27]. Of the remaining papers, eight were prospective controlled clinical trials, of which three were categorized as Oxford LoE 3 [34,35,50], four as Oxford LoE 4 [46,48,53,55], and one as Oxford LoE 5 [37]. Of the 16 matched case-control series, 14 were categorized as Oxford LoE 4 [20, 36, 38-41, 43, 44, 47, 49, 51, 52, 54, 56] and two as Oxford LoE 5 [42,45].…”
Section: General Information On Search Resultsmentioning
confidence: 99%
“…The impact of CovCP on the clinical status of patients with COVID-19 was also difficult to assess because the parameters evaluated in the studies with available results were inconsistent (Table 3). In some studies, no statistically significant improvements in clinical outcomes were observed [21,22,26,28,29,31,33,37,39,40,42,44,46,49,52,53]. In contrast, other studies showed benefits of CovCP in terms of disease progression [23,25,27], mitigation of hypoxia [30], World Health Organization (WHO) severity score [32], respiratory parameters [24,54], rate and time to clinical improvement [20,34], need for intubation [50], extubation rate [35], recovery time from critical illness [55], rate of MV and vasopressor support [51], rate of transfer to MV [41], and clinical status [38] in the overall study population or specific subgroups of patients with COVID-19.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, convalescent plasma [185,186] and monoclonal neutralizing antibodies [187,188] have relatively limited effects on COVID-19 evolution. Finally, neutralizing antibodies comprise a heterogeneous array of antibodies of different isotypes, affinities, kinetics, functionality, and specificities [104,105,184,189,190] making it unrealistic to assign a single effect to them.…”
Section: The Quest For Correlates Of Protectionmentioning
confidence: 99%